Wound Healing Potential of Virgin Coconut Oil in Combination With Extract of Neem Leaves (Azadirachta Indica L.) in Diabetic Rat Model - Luh Ade Wilankrisna,; Desak Made Lestari Dewi,; Burhannuddin,; Heri Setiyo Bekti,; Nur Habibah,; I Wayan Karta, (JST (Jurnal Sains dan Teknologi), 2024)
High blood sugar levels in DM can inhibit wound healing and increase the risk of infection. Diabetic ulcer therapy with commercial anti-inflammatory drugs is relatively expensive and has side effects. VCO and diamond leaf extract have the potential as an alternative therapy with anti-inflammatory effects, but further research is needed regarding the right dose. This study aimed to analyze the impact of VCO administration with supplementation of diamond leaf extract (Azadirachta indica L.) on IL-6 levels in wound healing of type 2 DM model rats. This research is a true experimental research with a post-test-only control group design. This study used 25 male mice which were divided into five groups, namely: group P1 5% Intaran leaf extract, P2 10% Intaran leaf extract, P3 15% Intaran leaf extract, negative control (NaCl 0.9%), and positive control (Povidone Iodine). Data were analyzed using the Shapiro-Wilk statistical test, followed by the One-Way Anova test, the confirmation test, and the LSD test. The results showed a significant difference in IL-6 levels between the treatment groups, as evidenced by the One Way ANOVA statistical test results. Considerable value was obtained in the test of IL-6 levels on day 4 Sig. 0.003 and day 14 Sig. 0,046. It can be concluded that the treatment group giving VCO supplementation with intern leaf extract at a concentration of 10% affects wound healing with a decrease in IL-6 levels on day 14. This study provides an important contribution to DM wound healing efforts by using affordable natural ingredients with low potential side effects.